Optimal crank arm length and body position for road sprint cycling performance - Christiansen, C.; Bradshaw, E. J.; Wilson, C. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of the current study was to examine the effects of body position and crank arm length (CAL) on power production in road sprint cycling. Six well trained male cyclists were tested in the standing and seated positions, and with three CALs of 18, 20 and 22 % of leg length whilst out of the saddle. A modified six second Wingate test on a Velotron ergometer was used to measure power (Watts) and cadence (rpm), and a Vicon MX system was used to measure the hip and lower limb kinematics of the pedal cycle. A 4% increase in power was observed when riding out of the saddle and a CAL set at 18- 20% of leg length was superior for this task. The coordination pattern employed was consistent between postures and with different CALs.